DIGITAL ESCAPISM: EXPLORING THE ROLE OF BEING K-POP FANS FOR YOUNG ADULT WOMEN - Rahmadani, Putri (Universitas Negeri Surabaya, 2025)
This study aims to explore how digital escape through K-pop serves as a coping mechanism for young adult women facing stress and personal challenges. Using content analysis and in-depth interviews with five female participants aged 20 to 25, this study focuses on individual experiences in accessing K-pop content, interacting in online communities, and developing hobbies related to K-pop, such as fan art and fan fiction. This research employs Abraham Maslow's hierarchy of needs theory as its theoretical framework, with an emphasis on the levels of love and belonging and self-esteem. The findings reveal that engagement in the K-pop world provides a safe and supportive space for participants to express themselves, build their identities, and receive emotional support online. This study highlights how popular culture and the digital context can function as significant coping mechanisms in the daily lives of young adult women. This study contributes to contemporary cultural studies and psychology by demonstrating that the K-pop world can serve as an alternative space for fulfilling the emotional and psychological needs of young adult women.